Urban Environment: a place of space restriction and discovery of new spaces - Cruz, Patrícia de Góes (Saúde e Sociedade, 2011)
Child growth is linked to environmental, social and cultural factors to which children relate in their daily experience. Children begin their relationship with the environment through the exploration of their body, interacting with the environment, changing and adapting themselves to it according to their needs, and this favors the development of their social identity. This work focused on understanding the social and physical environment experienced by children in a place of environmental degradation and restriction of space for their social activities. The approach that was used was qualitative research with the content analysis technique. Semi-structured interviews were performed with 20 mothers and guardians of children aged 6-10 years, and an operative group was also held with them. The results of this study indicated that, in an environment with restricted space and social vulnerability, children grow up experiencing constant physical or psychosocial risks. On the other hand, these children develop collective negotiation skills and a plasticity of social use of space in a significant way. Therefore, we conclude that in spite of the dense context marked by social and environmental vulnerability that is experienced on a daily basis at those places by the children, they incorporate, cognitively and affectionately, experiences that allow them to learn how to deal with the adversities they find everyday.